Burundi : Sixth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Requests for Extension of the Arrangement and Augmentation of Access: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burundi. (IMF Staff Country Reports; Country Report ;, 2011)
The Burundian economy is recovering but at a slower pace than previously expected, while inflation is expected to rise considerably. The macroeconomic outlook has been adversely affected by the surge in global food and fuel prices. Policies focused on the appropriate policy response to the food and fuel price shock, with a view to consolidating economic stability and further reducing poverty are required. Executive Directors urge the government to anchor medium-term fiscal policy to debt sustainability. Sustained growth depends on accelerating structural reforms.